2002
DOI: 10.1046/j.1365-313x.2002.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

In muro fragmentation of the rhamnogalacturonan I backbone in potato (Solanum tuberosum L.) results in a reduction and altered location of the galactan and arabinan side‐chains and abnormal periderm development

Abstract: In muro fragmentation of the rhamnogalacturonan I backbone in potato (Solanum tuberosum L.) results in a reduction and altered location of the galactan and arabinan side-chains and abnormal periderm development SummaryRhamnogalacturonan (RG) I is a branched pectic polysaccharide in plant cell walls. Rhamnogalacturonan lyase (eRGL) from Aspergillus aculeatus is able to cleave the RG I backbone at speci®c sites. Transgenic potato (Solanum tuberosum L.) plants were made by the introduction of the gene encoding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 53 publications
4
58
0
Order By: Relevance
“…Not only was the number of transformants low but also the level of enzyme expression in the transformed plants was low, indicating a strong selective pressure against plants expressing AnPGII. Similarly, the transformation efficiency of potatoes with the genes encoding rhamnogalacturonan lyase and arabinanase of A. aculeatus has been reported to be very low (Skjot et al, 2001;Oomen et al, 2002). Interestingly in a situation where we did not limit the effects of the enzyme activity by using tissue-specific promoters and/or specific targeting signals, the plant was capable of performing its own control of AnPGII by proteolytically processing and inactivating the enzyme.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Not only was the number of transformants low but also the level of enzyme expression in the transformed plants was low, indicating a strong selective pressure against plants expressing AnPGII. Similarly, the transformation efficiency of potatoes with the genes encoding rhamnogalacturonan lyase and arabinanase of A. aculeatus has been reported to be very low (Skjot et al, 2001;Oomen et al, 2002). Interestingly in a situation where we did not limit the effects of the enzyme activity by using tissue-specific promoters and/or specific targeting signals, the plant was capable of performing its own control of AnPGII by proteolytically processing and inactivating the enzyme.…”
Section: Discussionmentioning
confidence: 94%
“…Galactanase, rhamnogalacturonan lyase, and arabinanase from Aspergillus aculeatus, which attack RG-I, have been used to transform potatoes (Solanum tuberosum). Plants expressing galactanase displayed no altered phenotype (Oxenboll et al, 2000), while those expressing rhamnogalacturonan lyase had more wrinkled tubers than the wild type (Oomen et al, 2002) and those expressing arabinanase suffered serious developmental disruption and produced no side shoots, flowers, stolons, or tubers (Skjot et al, 2001).…”
mentioning
confidence: 99%
“…The altered HG network and reduced cell adhesion observed in the Cnr tomato mutant could be a consequence of disrupted arabinan deposition in this tomato cell wall (Orfila et al, 2001(Orfila et al, , 2002. A role for arabinans in anchoring pectin in the wall was suggested by these authors, but the decreased abundance and altered location of arabinan side chain when RG I was fragmented in muro by a rhamnogalacturonan lyase in transgenic potato plants indicated that cross-linkage between arabinans and other components of the wall is unlikely (Oomen et al, 2002). However, if the arabinans were preventing enzymatic hydrolysis of HG, as we propose here, their absence would produce loss of pectin network integrity without any direct attachment.…”
Section: Discussionmentioning
confidence: 96%
“…13 Furthermore, it has been shown that 'in muro' fragmentation of the RG1 backbone in Solanum tuberosum results in abnormal development of the periderm. 14 This suggests that these side chains may play at least some role in normal cell attachment and cell development. However, the real problem is that no obvious phenotypic differences between wild type and mutant plants (in which neutral side chains have been modified) have been observed.…”
mentioning
confidence: 99%